NEW STRATEGIES FOR STEM CELL MOBILIZATION - Roberto Lemoli (Mediterranean Journal of Hematology and Infectious Diseases)
Mobilized peripheral blood (PB) is widely used as source of stem cells (PBSCs) for autologous stem cell transplantation (ASCT). The use of cytokines, alone or in combination with chemotherapy (chemomobilization), is the most common strategy applied to mobilize and collect PBSCs. However, a significant proportion of cancer patients fail to mobilize enough PBSCs to proceed to ASCT. Plerixafor is a small molecule that reversibly and transiently disrupts the interaction between the chemokine receptor CXCR4 and its ligand CXCL12 (formerly known as stroma derived factor 1, SDF-1) leading to the rapid release of CD34+ hematopoietic stem cells from the bone marrow (BM) to PB. Plerixafor has been recently approved to enhance PBSC mobilization in patients with multiple myeloma or non-Hodgkin lymphoma and has been shown to be more effective than G-CSF alone. There is limited experience on combining plerixafor with chemotherapy plus G-CSF in patients who mobilize poorly. Current evidence suggests that the addition of plerixafor is safe and effective in the large majority of the patients with low blood CD34+ cell count after mobilization and/or poor yield after the first collection(s). Circulating CD34+ cells can be increased by several folds with plerixafor and the majority of the patients considered “poor mobilizers” can be successfully collected. Overall, its mechanism of action inducing the rapid release of CD34+ cells from the BM to the circulation makes plerixafor suitable for the ‘pre-emptive’ use in patients who are hard-to-mobilize.